HISTOPATHOLOGICAL CHANGES OF MICE LIVER THAT INDUCED BY ETHANOL EXTRACT OF ANT NEST TREE - Prasetyo, Yoga Eka; Merdana, I Made; Kardena, I Made; Sudira, I Wayan (Buletin Veteriner Udayana, 2019)
Anthill plants attracted many people as an alternative medicine because proven efficacious for treating tumor diseases, cancer, tuberculosis, stroke, coronary heart disease, diabetes mellitus, nosedleeds, ulcer, hemorrhoids, facilitate breastfeeding, increase stamina and sexual arousal. This study aimed to determine the effect of ethanol extract of the anthill plant to the mice liver histopathology. This study is an experimental laboratory. Twenty fourth male mice 10-12 weeks of age with a body weight of 25-35 grams were divided into 4 groups, each group consisting of 6 mice were given treatment that Control Group, Group I (doses 100mg/kg BW), Group II (doses 200mg/kg BW) and Group III (doses 300mg/kg BW) for 21 days. Hepatic histopathological changes were observed and assessed by histological damage in the form of infiltration of inflammatory cells, lipid degeneration and necrosis. Data were analyzed using statistical test of Kruskal-Wallis followed with Mann-Whitney Test (p<0.05). Kruskal-Wallis test result showed ethanol extract anthill very significant (p<0.01) effect on the incident of lipid degeneration, necrosis and infiltration of inflammatory cell of liver cells. Based on these result it can be concluded that the ethanol extract of anthill can cause histological changes in the liver of mice.